Dr. Mark Mofid — Deep Plane Facelift — San Diego - Mofid, Mark (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Mark Mofid, practicing in San Diego, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003046; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; san diego